Optimization Of Coconut Husk Fermentation By Pycnoporus Sanguineus Using Taguchi Method For Laccase Production - Fuad, Izzati Ahmad (2019)
Nowadays, enzymes have high demand in industry and laccase is one of them which present widely in nature. Laccase has an important role in biotechnology due to their ability to oxidize both phenolic and non-phenolic lignin related compounds. It also can be used to overcome environmental pollutions. To produce laccase enzyme, a fungal solid-state fermentation (SSF) process that uses lignocellulosic waste was introduced. This research aims to optimize the production of laccase from Pycnoporus sanguineus through one-factor-at-a-time (OFAT), Taguchi method and ANOVA by solid-state fermentation (SSF) of lignocellulosic waste. For the preliminary study, different types of lignocellulosic waste such as coconut husk, pine needle, rubber seed shell and sawdust were screened in order to select the most suitable substrate for laccase production. Coconut husk was proven to be the best substrate for laccase production compared to others, with the highest activity of 5134.25 U/L. After the screening process, studies continued on the effect of selected parameters on production of laccase using OFAT method namely; incubation day, substrate to water ratio (wt/vol), pH and temperature. The results showed that the best conditions for laccase production were at 18th days of incubation, pH 7, temperature of 30 ̊C, and 1:9 (wt/vol) of substrate to water ratio with the highest activity of 8747.4 U/L.In this study, further optimization by using Taguchi method was proposed by Minitab 18 Software at “larger is better” as a quality character was used. An L9 orthogonal array was constructed in optimization by using Taguchi method because it needs 9 experiments for 4 parameters operating at 3 levels. The 3 levels used in Taguchi method were obtained from the earlier study of OFAT method. The results showed that the maximum laccase production was obtained as 8747.6 U/L which was almost similar to the OFAT result. Taguchi method has shown that temperature is the most significant factor in optimizing the production of laccase with (36.31%) of percent contribution, followed by substrate to water ratio (wt/vol) (30.76%), incubation day (27%) and pH (5.92%). The final results showed that the maximum laccase production was obtained as 8698.1 U/L with a small value of percentage error (0.5%). The research findings demonstrated that environmental factors influence the fungi growth to produce a high activity of laccase. Selection of strain and substrate that capable of producing high concentrations of an enzyme and then optimize conditions for enzyme production are the important things to do. This is because, different strain, substrate and cultivation condition give a different yield of enzyme production. It is therefore not surprising that this enzyme has been studied intensively since the nineteenth century and yet remains a topic of intense research today.